ANALISIS KESALAHAN EJAAN PADA TEKS ANEKDOT - Juniarni Buuolo (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research was motivated by errors in writing anecdote texts by students. This is due to students' lack of interest in writing and students' lack of ability to express their ideas correctly according to the applicable spelling. Based on the results of interviews, students pay less attention to linguistic rules or rules when writing anecdotal texts. This research aims to describe the forms of spelling errors in anecdotal texts of class X SMA Negeri 1 Amandraya students. The approach used in this research is a qualitative approach with a type of descriptive research that requires solving problems based on existing data, analyzing and interpreting the data. The research results found that out of 25 students, 7 students did not make/no mistakes in writing the anecdote text, while 18 students made mistakes. The errors found were errors in the use of capital letters in 18 texts, errors in the use of words in 14 texts, errors in the use of commas in 11 texts, errors in the use of quotation marks in 14 texts, and errors in the use of question marks in 11 texts. Suggestion, the results of this research can be used as material for further research regarding the analysis of spelling errors in anecdotal texts for class X students of SMA Negeri 1 Amandraya for the 2023/2024 academic year.